Analisa Tingkat Pelayanan Pengguna Aplikasi Ojek Online terhadap Mahasiswa Universitas Muhammadiyah Semarang (Indonesian Journal of Civil Engineering Study, 2026)
The development of transportation technology has a significant impact on people's mobility, including in the student environment. Online motorcycle taxi applications are one of the practical, fast, and affordable transportation solutions. This study aims to analyze the level of service of online motorcycle taxi applications for students of the University of Muhammadiyah Semarang, with a focus on service quality, ease of use of the application, security, punctuality, and price and promo factors. The method used in this study is a quantitative method. Primary data were obtained through questionnaires distributed to 150 active students from various faculties. The analysis was carried out using descriptive statistics, including the calculation of mean, median, mode to evaluate user perceptions of online motorcycle taxi services. The results of the study showed that most respondents were satisfied with online motorcycle taxi services, with an average value 4 in the category of "Agree" to "Strongly Agree". The ease of application and punctuality are the main indicators of user satisfaction. In addition, the existence of promos and ease of access are also a special attraction for students. This study is expected to provide input for online motorcycle taxi service providers in improving service quality, as well as being an academic reference in the field of technology-based transportation.
Keywords: Online Motorcycle Taxi; Services; Students; Technology; Transportation